The Development and Evaluation of a Student Centred Reflective and Professional Electronic Portfolio for Pre-service Teachers - Pelliccione, Lina; Dixon, Kathryn; Dixon, Robert (Association for the Advancement of Computing in Education, 2004)
Technology must be used to reflect the most current thinking about education and its use should be as a common language for linking people and projects into the future. The development and implementation of electronic portfolios in the tertiary sector has the potential to meet such a challenge. This paper reports on the initial findings of a study which aimed to empower students to map and demonstrate their developing professional skills, knowledge and values through the use of electronic portfolios. The sample involved 30 first year students in a Bachelor of Education course in Western Australia. The findings revealed that the majority of students believed that it was possible to construct a personal portfolio electronically and that it should reflect personal works achieved over time. Students viewed the construction of the portfolio as a way of increasing their own skills in order to replicate a similar process in their own classroom environments.